The Creation of Cultural Heritage Towards the Development of a Modern Thai Architectural Identity - Horayangkura, Vimolsiddhi (Journal of Architectural/Planning Research and Studies (JARS), 2018)
There has been widespread criticism concerning the inappropriate application of traditional Thai characteristics to contemporary architectural designs, particularly to buildings of national significance such as the Supreme Court Building and the new Parliament Complex. Yet there are no obvious solutions to meet the demand for a modern Thai architectural identity. This research was undertaken according to the following objectives: 1) to investigate the appropriateness of current Thai architectural identity in modern society; 2) to seek guidelines for the creation of a modern Thai architectural identity; 3) to suggest development approaches for sustaining the creation of this identity; and 4) to use the development of a modern Thai architectural identity as an opportunity to support the creative economy. Thus, in this preliminary study physical surveys of buildings with various Thai characteristics were conducted, together with a literature review, with the intention to set up an information base for the formulation of a theoretical and analytical framework, as well as guidelines for the creation and development of a Thai identity for the architecture of modern society. This research primarily reveals that the various applications of Thai architectural characteristics are not very appropriate to the current social context - neither the traditional and applied Thai architectural styles, nor the abstract aesthetic approach. These findings urge for the reinvention of modern Thai architectural identity in the context of globalized architecture. Contemporary trends – economic, social, cultural and progressive technological - must be converged with deep-rooted cultural traditions in the attempt to reinvigorate Thai architectural identity. In this context, there has to be an interrelationship between contemporary style and indigenous wisdom. Concurrently, five major approaches have been proposed to promote sustainable development of identity: the generation of public consciousness; the reformation of the education system; the establishment of an Institution for Research and Development of Modern Thai Architectural Identity; the stimulation of a concern for Thai identity among practitioners; and lastly, the support and promotion of those with outstanding achievements in design and research. This research also outlines the opportunities that the creation of a Thai architectural identity could present for the creative economy. Lastly, a series of research questions have been formulated to be addressed in future research projects.